REFLEKSI EKLESIOLOGIS ATAS PERAN UMAT AWAM DALAM SEJARAH PEMBENTUKAN PAROKI SAKRAMEN MAHAKUDUS PERIODE 1989-2001 - KRISNA, KRISTOFORUS (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2022)
The history of the founding of the Blessed Sacrament Catholic Church is closely related to therole of Father Heijne, SVD. The church, which is located next to the Al-Akbar National Mosque,cannot be separated from the role of the laity who participate. Some of the problems during thechurch building process could be resolved with the help of the lay people. This is to say thatspeaking about the Church is not only about pastors at work, but also the role of the laity in thelife of the church. The reflection leads to the ecclesiological idea of the Church as a communityof God's people, in which every believer participates in building the life of the Church.